Smarandache curves for spherical indicatrix of the Bertrand curves pair - Süleyman Şenyurt; Yasin Altun; Ceyda Cevahir (Boletim da Sociedade Paranaense de Matemática, 2018)
In this paper, we investigate special Smarandache curves with regard to Sabban frame for Bertrand partner curve spherical indicatrix. Some results have been obtained. These results were expressed depending on the Bertrand curve. Besides, we are given examples of our results.